2022
DOI: 10.3389/fgene.2021.815160
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights Into the Population History and Biological Adaptation of Southwestern Chinese Hmong–Mien People

Abstract: Hmong–Mien (HM) -speaking populations, widely distributed in South China, the north of Thailand, Laos, and Vietnam, have experienced different settlement environments, dietary habits, and pathogenic exposure. However, their specific biological adaptation remained largely uncharacterized, which is important in the population evolutionary genetics and Trans-Omics for regional Precision Medicine. Besides, the origin and genetic diversity of HM people and their phylogenetic relationship with surrounding modern and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…These findings also supported that the Yao was closer related to populations belonging to the TK language family than the Miao and She [ 30 ]. Liu et al collected genome-wide SNP data from three representative Miao groups in Sichuan Province and merged them with data from 144 Miaos from 13 regions to comprehensively characterize the biological adaptations of the Miao people during the migration [ 31 ]. The findings revealed high genetic similarity among HM populations from different regions in southwestern China and Southeast Asia, but subtle genetic differences between each other.…”
Section: Introductionmentioning
confidence: 99%
“…These findings also supported that the Yao was closer related to populations belonging to the TK language family than the Miao and She [ 30 ]. Liu et al collected genome-wide SNP data from three representative Miao groups in Sichuan Province and merged them with data from 144 Miaos from 13 regions to comprehensively characterize the biological adaptations of the Miao people during the migration [ 31 ]. The findings revealed high genetic similarity among HM populations from different regions in southwestern China and Southeast Asia, but subtle genetic differences between each other.…”
Section: Introductionmentioning
confidence: 99%
“…Tibeto-Burman groups from Tibetan Plateau had the highest proportion of ancestry related to core Tibet Tibetan and Nepal Chokhopani, Mebrak, and Samdzong people [ 67 , 68 ]. The primary ancestral component of Hmong-Mien people from southwestern China was maximized in ancestry related to Miao and Yao people [ 69 ], and Austronesian-speaking people from Taiwan Island have more Ami/Atayal or ancient Hanben-related ancestry [ 41 ]. Han Chinese ancestry localized between the four ancestries mentioned above and showed a northern-to-southern genetic cline.…”
Section: Discussionmentioning
confidence: 99%
“…However, their fine-scale population history and their genetic relationship with the surrounding Hmong–Mien- and Sino-Tibetan-speaking populations have not been fully characterized, which are especially focused on the sharing of genome-wide haplotype data. Genetic studies of populations from the Yunnan–Guizhou Plateau regions have found enriched genetic diversity and complex mixed population genetic history ( He et al, 2019a ; He et al, 2019b ; Zhang et al, 2019 ; Liu et al, 2021a ; He et al, 2021b ; Liu et al, 2021b ; Chen et al, 2021 ). The detailed relationship between Maonan and modern and ancient neighboring populations needs to be characterized further.…”
Section: Introductionmentioning
confidence: 99%